Literary theory a practical introduction - Ryan, Michael 1951- (How to study literature, 2017)
Presents a comprehensive introduction to the full range of contemporary approaches to the study of literature and culture, from formalism, structuralism, and historicism to ethnic, gender, and science studies. This edition includes new sections addressing theoretical approaches to literature relating to cognition, emotion, evolution, and animals, humans, places; an expanded section on ethnic, postcolonial, and global studies; and greater attention paid to film and cultural texts to reflect contemporary trends. In addition, a variety of classic literary texts are newly considered in this edition, including The Great Gatsby, The God of Small Things, Frankenstein, and more. Vividly demonstrating how the same classic and contemporary texts - when approached from different perspectives - can lead to surprisingly varied interpretations, chapters reveal illuminating insights into literary texts ranging from King Lear and Alice Munro's short stories to the poetry of Elizabeth Bishops, along with noted films from Citizen Kane to Run, Lola, Run. The third edition is an invaluable resorce for anyone tasked with the writing of a critical essay - while allowing all to gain a much deeper appreciation of the literature.